Salivary biomarkers associated with obstructive sleep apnea: a systematic review. (1st February 2021) - Bencharit, Sompop; Redenz, Robert G.; Brody, Erica R.; Chiang, Harmeet
ABSTRACT: Introduction : This study aimed to define and characterize current literature describing salivary biomarker changes with the goal of improving diagnosis and treatment outcomes for sleep apnea. Area Covered : A search of six databases yielded 401 peer-reviewed articles published through October 2019 corresponded to 221 unique references following deduplication. Twenty studies were selected. The sample size ranged from 17 to 99. The samples were mostly whole saliva and selected glandular areas. Expert Opinion : Most targeted studies focused on the level of salivary cortisol and ɑ-amylase. One study used RNA transcriptome analysis of 96 genes. Only two explored novel targets using mass spectrometry. ɑ-amylase, myeloperoxidase, and IL-6 were among those biomarkers found associated with OSA. Cytokeratin, CystatinB, calgranulin A, and alpha-2-HS-glycoprotein are upregulated in OSA patients based on non-targeting mass spectrometry. Salivary cortisol and ɑ-amylase and others appeared to be associated with severity of OSA and OSA treatment. There were inconsistencies in saliva collection and processing protocols. More studies are needed in exploring novel biomarkers to examine if these biomarkers are capable of diagnosing and monitoring OSA through proteomics or transcriptomics. Salivary biomarkers have a potential to be a noninvasive measure for the disease diagnosis and treatment outcome monitoring for sleep apnea.